Anti-hyperglycemic Effect of Paeonia Lactiflora Pall Roots Extract on normal rat model - Nisreen Abdul karirm Abdul Aali misanjas ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
In the present  study antihyperglycemic activity was evaluated in  ethanolic root  Extract of Paeonia lactiflora in noroglycemic Rats. Extract at Dose 250mg/Kg had Effect non significant different (p<0.05) to glimepiride at Dose  8mg/Kg, 90 minutes  after Glucose Load Peonia  Lactiflora Pall a significant blood sugar lowering Effect The antihyperglycemic activity of of  Peonia Lactiflora Pall  was designed in normoglycemic Rats  .preparatory qualitative chemical screening Indicate the presence of "saponins,tannins, ,triterpens,flavonoids, and glycosides in ethanolic Root Plant". LD50  doses ethanolic root Plant was studied Results this study showed no mortality rate from ascending doses until 2gm/kg B.Wt. was occurred